So, I was watching this video by blackpenredpen where he mentions that $$\sqrt {a-\sqrt {a+\sqrt {a-\sqrt {a+\sqrt {a-\sqrt {a+\ldots}}}}}}=\frac {\sqrt {4a-3}-1}2$$ so I wanted to try and prove it myself.

Let $\sqrt {a-\sqrt {a+\sqrt {a-\sqrt {a+\sqrt {a-\sqrt {a+\ldots}}}}}}=x$
But$\sqrt {a-\sqrt {a+\underbrace{\sqrt {a-\sqrt {a+\sqrt {a-\sqrt {a+\ldots}}}}}_x}}=x$
$\therefore \sqrt {a-\sqrt {a+x}}=x$
$a-\sqrt {a+x}=x^2$
$x^2-a=-\sqrt {a+x}$
Note that this is of the form $y^4+py^2+qy+r=0$ so we can use Ferrari-Cardano.

We need to find a $z$ such that $(2z-p)y^2-qy+(z^2-r)$ has a discriminant of $0$. The discriminant of $(2z-p)y^2-qy+(z^2-r)$ is equal to $q^2 - 4(2z - p)(z^2 - r),$ which simplifies to $8z^3 - 4pz^2 - 8rz + (4pr - q^2) = 0$

Substituting values from $x^4-2ax^2-x+a^2-a=0$ into $8z^3 - 4pz^2 - 8rz + (4pr - q^2) = 0$ gives us
$8z^3-4\cdot(-2a)\cdot z^2-8\cdot(-a)\cdot z+\left(4\cdot (-2a) \cdot (-a) - (-1)^2 \right)=0 \implies 8z^3+8az^2+8az+(8a^2-1)=0$

Using Cardano's formula, or in my case Wolfram Alpha, we get that $$z_1 = \frac {\sqrt [3]{-16 a^3 - 144 a^2 + 3 \sqrt 3 \sqrt {256 a^5 + 512 a^4 + 224 a^3 - 288 a^2 + 27} + 27}}{6\sqrt[3]2} - \frac {192 a - 64 a^2}{48\cdot 2^{\frac 23} \sqrt [3]{-16 a^3 - 144 a^2 + 3\sqrt 3 \sqrt {256 a^5 + 512 a^4 + 224 a^3 - 288 a^2 + 27} + 27}} - \frac a3$$

I simply can not solve that quintic and continue as it is already too cluttered. Was there a mistake in my problem or is there any other way to do it? Also, I am sincerely sorry but I am not sure how to tag this question.

Edit $1:$

After Ross Millikan's answer, I snooped around in the comment section of the video and found someone who found that it is true using alternating root series. Was his proof correct as $\frac {\sqrt {4a-3}-1}2$ does not seem to have real values for $a \lt \frac 34$? Thank you!



$x^4-2ax^2-x+a^2-a=0$ can be factorised as $(x^2-x-1)*(x^2+x+1-a)$. You'll get the desired answer from the right factor $(x^2+x+1-a)$.

  • 1
    $\begingroup$ very neat solution (+1) $\endgroup$ – G Cab Oct 22 '18 at 23:59
  • $\begingroup$ @GCab thank you $\endgroup$ – Ankit Kumar Oct 23 '18 at 4:35

It's wrong! You can try $a=0$.

Also, try $a=1$.

If your sequence converges then we need to solve the following equation $$\sqrt{a-\sqrt{a+x}}=x.$$ Let $a+x=y^2,$ where $y\geq0$.

Hence, $$y^2-x=a$$ and $$x^2+y=a,$$ where $x\geq0$ and $a\geq0.$

Thus, $$y^2-x^2-x-y=0$$ or $$(x+y)(y-x-1)=0.$$

If $x+y=0$ so $x=y=a=0$ and your formula is still wrong.

If $y=x+1$ then $x^2+x+1-a=0,$ which gives $$x=\frac{-1+\sqrt{4a-3}}{2}.$$ Now, since $x\geq0$, we have $$\frac{-1+\sqrt{4a-3}}{2}\geq0,$$ which gives $a\geq1$.

But for $a=1$ our sequence divergences and it should be $a>1$.

  • $\begingroup$ Oh, I never realised that! But does it hold for other values of $a$? He solved $\sqrt {5-x}=5-x^2$ in that video and used that identity to find the answer. Was he wrong? $\endgroup$ – Mohammad Zuhair Khan Oct 22 '18 at 18:46
  • $\begingroup$ @Raptor I added something. See now. $\endgroup$ – Michael Rozenberg Oct 22 '18 at 18:57
  • $\begingroup$ Essentially, you both got the same answer, except that he used the equation. Could it be that it only holds for $a\gt \frac 34?$ $\endgroup$ – Mohammad Zuhair Khan Oct 22 '18 at 18:59
  • $\begingroup$ @Raptor Do you say about the equation $\sqrt{a-\sqrt{a+x}}=x$? $\endgroup$ – Michael Rozenberg Oct 22 '18 at 19:03
  • 1
    $\begingroup$ +1 Lovely solution, thanks! $\endgroup$ – A-Level Student Oct 25 '20 at 14:10

If the nested radical converges to $x$, $$\sqrt{a-\sqrt{a+x}}=x,$$



This should be verified by $x=\dfrac{\sqrt{4a-3}-1}2$. Indeed,


We can show that

$$\sqrt{a-\sqrt{a+x}}-x$$ is monotonic, so that there is at most one solution.

Anyway, this still doesn't prove that the nested radical converges.


Here's an easier solution that doesn't require you going out to a fourth degree polynomial. Let $\sqrt {a-\sqrt {a+\sqrt {a-\sqrt {a+\sqrt {a-\sqrt {a+\ldots}}}}}}=x$, $-\sqrt {a+\sqrt {a-\sqrt {a+\sqrt {a-\sqrt {a+\sqrt {a-\ldots}}}}}}=y$.

Then $x^2 - y = a$, and $y^2-x = a$. Subtracting these two equations, we have that $x^2 - y^2 + x-y =0 \implies (x-y)(x+y+1) = 0$. Since $x \neq y$ unless both are equal to zero, $x+y = -1$. Adding these equations, we have $x^2 +y^2 - (x+y) = 2a$, and substituting everything in, we have $x^2 + x = a-1$, which we can evaluate via the quadratic formula to $x=\frac{-1+\sqrt{4a-3}}{2}$, where we have ignored the other solution since it is always negative.

  • $\begingroup$ Thank you for your answer. Unfortunately, that answer is already linked in my question in the edit section. $\endgroup$ – Mohammad Zuhair Khan Oct 23 '18 at 4:38

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.